Cost-Benefit Analysis and the Theory of Public Finance - Musgrave, Richard A. (Journal of Economic Literature, 2016)
AHEORY of public finance remains unsatisfactory unless it comprises both the revenue and expenditure sides of the fiscal process. The classical (RicardoMills-Edgeworth-Pigou) tradition of a taxation-only view neglected this axiom. Holding expenditures unproductive, or disregarding them altogether, the task was to arrange taxes so as to impose equal (or least total) sacrifice. As a theory of taxation, this approach collapsed with the old welfare economics; and as a theory of public finance, its exclusive concern with taxation bypassed the central problem of how to allocate resources for the provision of social goods. Subsequently, various attempts were made to combine the revenue and expenditure sides in a more satisfactory system. We shall note these briefly, and then consider how cost-benefit analysis fits into the picture.